Contribución a la filogenia de Philonotis Brid. (Bartramiaceae Schwaeger: Flavonoides de las secciones Catenularia (C. Müll) Pat. y Euphilonotis Limpr. - López-sáez, José Antonio; Velasco-negueruela, Arturo; Pérez-alonso, María José (Botanica Complutensis, 1996)
Sin resumen